2009
DOI: 10.1002/art.24433
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis joint progression in sustained remission is determined by disease activity levels preceding the period of radiographic assessment

Abstract: Objective. Joint damage is related to disease activity in rheumatoid arthritis (RA), but the degree of its progression and the temporal associations between disease activity and joint damage are unclear. The aim of this study was to evaluate whether there is a latency in the effect of disease activity on radiographic progression in patients with RA.Methods. Data were obtained from the PREMIER trial, a 2-year randomized, controlled clinical trial of adalimumab plus methotrexate versus methotrexate alone or adal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 35 publications
(32 reference statements)
2
81
0
3
Order By: Relevance
“…Despite these limitations, the findings of this work are consistent with those of a growing body of other studies and recent recommendations for RA management 1,2,3,15,16,26,29,30,31,32 . The present data suggest that adjustment of therapy in the population evaluated in this study should be considered at Week 12 for patients with inadequate initial clinical response (defined as DAS28 change < 1.2).…”
Section: Rheumatologysupporting
confidence: 87%
“…Despite these limitations, the findings of this work are consistent with those of a growing body of other studies and recent recommendations for RA management 1,2,3,15,16,26,29,30,31,32 . The present data suggest that adjustment of therapy in the population evaluated in this study should be considered at Week 12 for patients with inadequate initial clinical response (defined as DAS28 change < 1.2).…”
Section: Rheumatologysupporting
confidence: 87%
“…Therefore the first 4 years may be a ''window of opportunity'' to prevent disease progression to functional disability. Impaired physical function in patients with RA is governed by various factors, but Smolen et al [18,19] reported 186-194 191 that HAQ is composed of disease-activity-related HAQ and damage-related HAQ; changes in activity HAQ were mainly due to changes in disease activity, although there was little damage during a short-term therapeutic intervention, whereas HAQ would worsen with increasing damage. Actually, HAQ-DI similarly decreased in a group of patients whose baseline mTSS was [73.0 and in another group with mTSS \73.0, indicating that HAQ improvement did not depend on baseline mTSS and that etanercept improved activity-related HAQ.…”
Section: Discussionmentioning
confidence: 97%
“…Remision at one point must be differentiated from sustained remission (>18 months), the last one being correlated to joint scores, radiologic progression, and residual disfunction reduction [99,100]. This information is important when readjustment of treatment strategy (tapering/ arrest) is discussed [77,101].…”
Section: Gradementioning
confidence: 99%